As pontas de uma estrela: poéticas do silêncio em Macabéa e Ponciá - Cristiane Felipe Ribeiro de Araujo Cortes (2016)
This research seeks to outline a silent poetry grounded on possible readings based on wordless / silenced subjects. Our work has dwelled on texts by female authors and on works dealing with gender and subaltern relations. From a wide-ranging array of possibilities, we chose to work with Clarice Lispectors A hora da Estrela as well as Ponciá Vicêncio and the short novel Macabéa, Flor de Mulungu both by Conceição Evaristo. These selections rationale is that in all these works a literary discourse will translate these kept-down womens silencing in a very peculiar way. Moreover, there is a direct straightforward dialogue between the character Macabéa (in A hora da estrela) and Conceição Evaristos Flor de Mulungu short story. Inter-character closeness is due to both to the alterity theme itself and to the fact that these females are typically oppressed in major cities, yet they keep a rather peculiar silence. Poetry of silence is a concept linked to literary performance such silence seen as a sharply piercing outcry reverberating a lifetime of absence and emptiness, but never submission. Silence in this case will be deemed to be power. It will also mean a hopeful possibility to stand up against capitalist societies ramming down our throats a transformation of essence into sheer merchandise indeed, a firefly adamantly resisting amidst post-modernitys enticing limelight. This leads the reader to reflect on these females silencing, as an exercise of both alterity and acknowledgement.